Adhatoda vasica and Calotropis procera as a resource of novel chemical compounds, their biological bioluminescence assay, and investigation of morphological features of bacterial growth through advanced technologies. Issue 5 (25th December 2021) - Ahmed, Waseem; Azmat, Rafia; Chendouh‐Brahmi, Nabila; Hussain, Ijaz; Ahmed, Rasheed; Ahmad, Zahoor; Qayyum, Abdul; Moin, Sumeira; Bibi, Yamin
Abstract: This article reports the three principal groups of compounds for the first time from Adhatoda vasica and Calotropis procera plants species using nuclear magnetic resonance methods in which aliphatic, oxy heterocyclic, and tannins compounds were detected from these plants. The leaves of both species were subjected to testing tyrosinase inhibition and antioxidant activities. ATP bioluminescence use for indirect measurement of the amount of organic residue on the surface of the leaves that provide support to microbial growth. The distinguishing characteristics and intraoperative findings of bacterial diseases involved in treatments were conducted against the positive and negative microbial strains using a scanning electron microscope (SEM). The methanolic extracts of leaves of both species were applied to bacterial strains through broth microdilution method to determine the minimum inhabitation concentrations (MICs) for both species. It was concluded that both plants are a rich resource of bioactive compounds. Their extract may also be used to treat various bacterial diseases and in drug manufacturing. Highlights: New chemical compounds of oxy‐heterocyclic, aliphatic, and tannins derivatives are isolated from herbal plants as a source of various drugs. 1 H NMR spectrum and 13 C NMR spectrum of each new derivate were calculated. NMR‐spectral analysis of new compound of chemistry class was studied and further applied in various bacterial strains. Tyrosinase inhibition property of bacteria strains by application of active compounds on these strains. Agar overlay bioassays were used to evaluate intercellular morphological features of strains applied on extracts by electron microscope (SEM). a‐Glucosidase inhibition assay determined with antioxidants activity through FRAP assay methods. Abstract :